Preferences of Young Consumers in Bogor City in Consuming Honey during the Covid 19 Pandemic - N. H. Rachmani; A. Apriantini; L. Cyrilla ENSD (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2023)
During the COVID-19 pandemic, people’s habits in consuming highly nutritious food increased, especially to increase the body’s immunity. Consuming honey is one of the way because it has high content and boosts immunity. Research on consumer preferences in consuming honey was carried outto determine the level of consumer preference. Respondents of as many as 108 people were selected with an age range of 20 to 30 years and domiciled in Bogor City, and the sample was selected purposively. Respondents chose to consume honey with a brand and packaging they are interested in that is plastic bottles, because of the ease of distribution and storage. This type of honey consumes as much as 34.8% of forest honey. Respondents were 29.6% more likely to consume honey once a month. Consumers choose honey packaged using plastic bottles, 51.9%. Honey consumption is most often done by consuming honey alone without adding any food. Consumer decision-making is influenced by factors on the level of consumer preference for a product, so it is necessary to conduct research to determine consumer preferences.